Determinants of Industrial Property Transfer to the Productive Sector in Colombian Public Universities - Morales Rubiano, María Eugenia; Sanabria Rangel, Pedro E.; Plata Pacheco, Paola A. (Cuadernos de Administración, 2014)
The Colombian public university poses diverse obstacles to efficiently interact with the production sector; some of these are related to their internal capacities, but others to the regulatory framework that governs them, as well as the conditions of the context. The aim of this article was to make evident the factors that have influenced upon the university transference of industrial property onto the productive sector. For this, a literature and documentary review was conducted of national and international experiences in transference starting from patents and utility models; semi-structured interviews were carried out in three Colombian public universities of the chiefs of liaison units, innovators who have developed patents, and personnel in companies benefitting from the transference. It was found that although during the last decade processes to transfer research results have improved, work is still needed on the appropriation of knowledge by the beneficiaries because in most cases they are not involved with the process from the beginning, it is still in the development stage, or research processes have been closed without the culmination of transference.